Bridging theory and practice in child welfare education: preparing students for practice - Hansen, Heidi Aarum; Bjørktomta, Siv-Britt; Gerdts-Andresen, Tina (European journal of social work, 2025)
A challenge in social work education is developing courses that effectively train students in the practical child welfare skills necessary to manage complex situations with families in vulnerable contexts. This study explores how practical, subject-integrated teaching methods were perceived to support critical reflection and the development of professional competence in child welfare work. The research focuses on an eight-week course within a Norwegian university-based child welfare programme, where students are trained to specialise in practice. Various teaching methods, including discussion-based seminars and real-life case studies from municipal child services, are employed to support learning and develop practical decision-making skills. The data were collected from 239 students participating in the course during the latter half of their second year in the bachelor’s programmes in Child Welfare and Social Work. Thematic analysis reveals that the course structure was experienced as fostering deeper professional reflection and enhancing students’ awareness of professional assessments. A significant aspect was the emotional work. The findings highlight the importance of instructors with hands-on child welfare experience, emphasising their role in bridging theoretical knowledge with practical application and reinforcing students’ preparedness for real-world social work practice.